Photo-physicochemical characterization and in vitro Photodynamic Therapy Activity of Phthalocyanine-Graphene Quantum Dots Conjugates - Nene, Lindokuhle Cindy (Rhodes University, Faculty of Science, Department of Chemistry, 2020)
This thesis reports on the preparation of several differently substituted Zn(II) phthalocyanine (Pc) complexes and their respective graphene quantum dots (GQDs) conjugates. In addition, Pc complexes substituted with biologically active molecules used in cancer therapeutics, namely: benzothiazole and morpholine, were also prepared and conjugated to GQDs. The photo-physicochemical properties were determined for both the complexes and their respective conjugates including the fluorescence/ triplet quantum yields and lifetimes as well as the singlet oxygen generating abilities. Upon conjugation to GQDs, the fluorescence of the Pc complexes decreased (insignificant decrease in some cases), with an increase in the triplet quantum yields. However, the singlet quantum yields of the Pcs in the conjugates did not show an increase with the increase in the triplet quantum yields. This is suspected to be due to the screening effect. The cytotoxicity of the complexes in vitro decreased upon conjugation, as a result of reduced actual number of Pc units provided in the conjugate for therapy. An increase in the efficacy upon quaternization was observed, and a relatively better performance was also observed for the cationic complex in combination with the biotin- functionalized GQDs, 7-GQDs-Biotin. Moreover, the cellular uptake of 7-GQDs-Biotin over 24 h was relatively high compared to complexes alone and other Pcs-GQDs conjugates.
Keywords: Photochemotherapy; Cancer -- Chemotherapy; Quantum dots; Graphene; Nanomedicine